The Widening, Deepening, and Lengthening of the Seven Mountains Mandate (7MM) Network: The Role of Network Apostolic Leadership - Fernando Mora-Ciangherotti (Religions)
This article describes the leadership and organizational elements that have made the Seven Mountains Mandate (7MM), one of the main doctrines of the Apostolic Restoration Movement (ARM), a very adaptable, simple to explain, and feasible to implement message and portable practice, which can be started at the local level and expand progressively to acquire regional and national dimensions. A new classification of apostolic networks is proposed in this article and a partial map of some of the networks that participated in the expansion of the 7MM is presented. Additionally, using definitions from network leadership theory, it is shown how different types of leaders, who function as horizontal connectors in apostolic networks, such as conveners, catalysts, mobilizers, facilitators, weavers, provocateurs, illuminators, hosts, and curators, contribute to the diffusion of the 7MM by promoting its global Widening, Deepening, and Lengthening (WDL). The article first describes the evolution of the church from denominations to networks and how the ARM adopted the network organizational structure that serves as a channel for the diffusion of the 7MM. Cases from the USA, Guatemala, Zambia, and Venezuela are used as examples to demonstrate how the 7MM’s expansion, or Widening (W); its contextualization and adaption, or Deepening (D); and its sustainability, reproduction, and evolution, or Lengthening (L), occur globally based on the network nature of the ARM and the network leadership enacted in the process.